Pengaruh Citra Merek Dan Kualitas Produk Terhadap Minat Beli Konsumen Pada Produk Minuman Vitamin C (Studi Kasus Pada Produk You C 1000 Di Kota Samarinda) - AdisAdisthy Shabrina Nurqamarani3, Dinda Tri Hadiah H.Mulyadi (EKONOMIA, 2020)
Beverage products in this globalization era are increasinglyÂ competitive particulaly on You C 1000 vitamin C beverage products as one of the less desirable beverage products among consumers. This can be seen in the data on the results of the index of the top brands in 2014-2017, You C 1000 is in fourth position.This study aims to determine influence of brand image and product quality on buying interest both partially and simultaneously. The sampling method uses probability sampling technique with simple random sampling method. The number of samples in this study were 100 respondents in the city of Samarinda who collected and knew product You C 1000. The analysis tool uses multiple linear regression.According to t test result, there is a significant and positive influence between brand image and buying interest in You C 1000 product in Samarinda City. There is a significant and positive influence between product quality and buying interest in You C 1000 product in Samarinda City. The results of the F test show there is a significant and positive influence between the variables Brand image (X1) and Product Quality (X2) simultaneously towards Purchase Interest (Y)on You C 1000 products in Samarinda City. This research recommends further researcher to add more variables and also for companies should maintain brand image and product quality on You C 1000 products